Graphene Nanoribbons Elicit Cell Specific Uptake and Delivery Via Activation of Epidermal Growth Factor Receptor Enhanced by Human PapillomaVirus E5 Protein - Chowdhury, Sayan Mullick (2014)
Ligands such as peptides, antibodies or other epitopes bind and activate specific cell receptors, and are employed for targeted cellular delivery of pharmaceuticals such as drugs, genes and imaging agents. Herein, we show that oxidized graphene nanoribbons, non-covalently functionalized with PEG-DSPE (1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N[amino(polyethyleneglycol)]) (O-GNR-PEG-DSPE) activate epidermal growth factor receptors (EGFRs). This activation generates predominantly dynamin-dependent macropinocytosis-like response, and results in significant O-GNR-PEG-DSPE uptake into cells with high EGFR expression. Cells with an integrated human papillomavirus (HPV) genome also show increased uptake due to the modulation of the activated EFGR by the viral protein E5. We demonstrate that this cell specific uptake of O-GNR-PEG-DSPE can be exploited to achieve significantly enhanced drug efficacies even in drug resistant cells. These results have implications towards the development of active targeting and delivery agents without ligand functionalization for use in the diagnosis and treatment of pathologies that overexpress EGFR or mediated by HPV.